CD34+/CD38− acute myelogenous leukemia cells aberrantly express Aurora kinase A. Issue 11 (10th June 2013) - Yang, Jing; Ikezoe, Takayuki; Nishioka, Chie; Nobumoto, Atsuya; Udaka, Keiko; Yokoyama, Akihito
Abstract : We previously showed that Aurora kinase A (AURKA) is aberrantly expressed in acute myelogenous leukemia (AML) cells when compared to bone marrow mononuclear cells isolated from healthy volunteers. We have also shown that CD34 + /CD38 − AML cells, one of compartments enriched for leukemia stem cells in most leukemia subgroups, were relatively resistant to cytarabine‐mediated growth inhibition when compared to their CD34 + /CD38 + counterparts. Our study attempted to identify therapeutic targets in CD34 + /CD38 − AML cells and found that CD34 + /CD38 − AML cells isolated from patients ( n  = 26) expressed larger amounts of AURKA than their CD34 + /CD38 + counterparts and CD34 + normal hematopoietic stem/progenitor cells isolated from healthy volunteers ( n  = 6), as measured by real‐time reverse‐transcriptase polymerase chain reaction. Blockade of AURKA by the specific inhibitor MLN8237 or a short hairpin RNA (shRNA) against AURKA significantly inhibited proliferation, impaired self‐renewal capability and induced apoptosis of CD34 + /CD38 − AML cells, in association with modulation of levels of Bcl‐2 family member proteins. Importantly, inhibition of AURKA in CD34 + /CD38 − AML cells by MLN8237 or an shRNA significantly impaired engraftment of these cells in severely immunocompromised mice and appeared to prolong their survival. These results suggest that AURKA is a promising molecular target to eliminate chemotherapy‐resistant CD34 + /CD38 − AML cells. Abstract : What's new? Acute myelogenous leukemia (AML) is orchestrated by a subset of self‐renewing leukemia stem cells (LSCs). CD34 + /CD38 − cells enrich for LSCs and are resistant to conventional anti‐leukemia agents. This study reports that CD34 + /CD38 − AML cells expressed larger amounts of Aurora kinase A (AURKA) than their CD34 + /CD38 + counterparts and CD34 + HSPCs. AURKA inhibition by MLN8237 or a shRNA significantly inhibited proliferation, impaired self‐renewal capability, and induced apoptosis of CD34 + /CD38 − AML cells. It also significantly impaired CD34 + /CD38 − AML cell engraftment in severely immunocompromised mice and appeared to prolong mice survival. AURKA is thus a promising molecular target to eradicate chemotherapy‐resistant CD34 + /CD38 − AML cells.